Activation of human leucocyte procollagenase by rheumatoid synovial tissue culture medium. - Wize, J (1975)
Production of a factor activating leucocyte procollagenase by tissue culture of rheumatoid synovium was shown. The activator was isolated, partly purified, and shown to be thermolabile, nondialysable, and had no activity toward casein, haemoglobin, histones, and PZ-peptide. The activity of the activator was partly decreased by trypsin.